Measurement and Risk Analysis of Ozone (O3) Concentrations in the 9 MeV and 12 MeV Electron Mode LINAC - Nur Khasanah; Raehanah; Bunawas; I Wayan Ari M; Rinarto Subroto; Lalu Sahrul H; Paramita Putri A; Dia Ulfariah (Postgraduate, University of Mataram, 2024)
This study investigates potential non-radiation hazards, specifically Ozone (O3) production, during Linear Accelerator (LINAC) electron mode radiotherapy. The research uses experimental measurements to determine Ozone concentration in the LINAC patient waiting room and control room. Measurements are taken assuming a Â±2-hour delay in one working day, using 9 MeV and 12 MeV energy, 400 MU dose rate, and illumination angles of 0o, 90o, and 270o. Maximum Ozone concentrations in the LINAC patient waiting room and control room are found to be 6.6 ppb (12 MeV) and 8.3 ppb (12 MeV), respectively. These concentrations fall below the chemical threshold limit and are deemed safe for human exposure. Notably, potentially detectable Ozone levels are observed in the LINAC banker. Overall, this research highlights the importance of monitoring Ozone levels to ensure the safety of both patients and personnel in LINAC facilities.